2013
DOI: 10.1590/s0104-66322013000200012
|View full text |Cite
|
Sign up to set email alerts
|

Modification of PSf membrane nanostructure using different fabrication parameters and investigation of the CO2 separation properties of PDMS-coated PSf composite membranes

Abstract: -The effects of preparation parameters on the performance and morphology of polydimethylsiloxane/ polysulfone (PDMS/PSf) membranes were investigated. The PDMS layer is mainly used for sealing the defects of the PSf selective layer. The membrane morphologies were characterized by using scanning electron microscopy (SEM). The CO 2 /CH 4 separation performance of membranes was studied by a pure gas permeation experimental set up. According to the SEM results, decreasing the water/N,N-dimethylacetamide (DMAc) rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 45 publications
4
17
0
Order By: Relevance
“…Membrane technology plays an important role in various environmental and energy processes, such as CO 2 capture (Zou and Ho, 2008;Hussain and Hägg, 2010;Brunetti et al, 2010;Yang et al, 2008), biogas upgrading (Deng and Hägg, 2010;Makaruk et al, 2010;Pakizeh et al, 2013;Momeni and Pakizeh, 2013), natural gas sweetening (Bernardo et al, 2009;Peters et al, 2011;Baker and Lokhandwala, 2008), and hydrogen production (Sà et al, 2009;Clem et al, 2006) and can potentially compete with some traditional separation methods in terms of energy requirements and economic costs (Xuezhong and Hägg, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Membrane technology plays an important role in various environmental and energy processes, such as CO 2 capture (Zou and Ho, 2008;Hussain and Hägg, 2010;Brunetti et al, 2010;Yang et al, 2008), biogas upgrading (Deng and Hägg, 2010;Makaruk et al, 2010;Pakizeh et al, 2013;Momeni and Pakizeh, 2013), natural gas sweetening (Bernardo et al, 2009;Peters et al, 2011;Baker and Lokhandwala, 2008), and hydrogen production (Sà et al, 2009;Clem et al, 2006) and can potentially compete with some traditional separation methods in terms of energy requirements and economic costs (Xuezhong and Hägg, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This result was in tandem with the report by Firpo et al 25 that the permeability shows a strong decrease with increase in thickness but the selectivity does not change significantly in its value. Pakizeh et al 26 reported that CO 2 molecules are absorbed at a high level on the skin layer surface and can then diffuse through the dense layer of the membrane. Therefore, the CO 2 permeability is governed by the skin layer thickness.…”
Section: Effect Of Thickness On Gas Permeation Performancementioning
confidence: 99%
“…Based on the literature, 18 tetraethyl orthosilicate was used as a crosslinker in PDMS solution to aid the crosslinking between PDMS and PSF chains. 20 wt % PDMS solution was prepared with n-hexane with the addition of 1 wt % crosslinker.…”
Section: Modification To Composite Membranementioning
confidence: 99%
“…Better performance in dip-coated membranes was attributed to penetration of PDMS into membrane pores during the immersion of membrane into PDMS, while in film casting PDMS was cast on membrane top surface only with a lower probability of pore filling by PDMS. Pakizeh et al 18 developed a PDMS/polysulfone (PSF) composite membrane by film casting and investigated CO 2 separation properties of the developed membrane under the effect of preparation parameters. Methanol, ethanol, and water were used as a coagulant, and it was reported that use of methanol as a coagulant resulted in less selective membranes.…”
Section: Introductionmentioning
confidence: 99%